Design and Force Analysis of Cannon Drum Transmission System - Liu Jie; Li Hui; Li Qiang (Jixie chuandong)
On the basis of analysis of the future development direction of naval gun system and the study of existing domestic and international shell-feeding system,learn from the desirability of them,an effective and feasible scheme model is established,the overall structure is determined.Through comparing and analyzing the advantages and disadvantages of different transmission mechanism,the gear transmission mechanism connecting by rotary supporting is adopted for the cannon drum.The rotary inertia of cannon drum rotating part is calculated and according to the design of motion law,the input torque of transmission gear when the cannon drum full load operation is calculated.At the same time,the dynamics simulation analysis for cannon drum full load model is carried out.The transmission gear input moment of force and the power time course curve are obtained.The important reference of type selection for the cannon drum driving device motor and reducer is provided.